Ezoterizmo transformacijos šiuolaikinėje kultūroje - Švilpienė, Dovilė (Literatūra, 2010)
The article concentrates on phenomena of Esoterism in contemporary culture, tries to reveal its variations and spread in the second half of the XXth century. The contemporary writer and publicist Jurga Ivanauskaitė is implicated in the context of the theme. Article is inspired by the majority expressions called Postmodernism: secularization, the fade of transcendental dimension, crisis of Religion, upheaval of traditional values that all together coincide with the new spread of Esoteric thought towards the end of the XXth century and beginning of the XXst century. The Postmodernism is even called an Egsoteric form of antecedent esoteric Modernism. The historical comparative method as well as theoretic-analytic are considered to be the most fertile to reveal changes that inspired the transformation in relations between sacrum (lat. sanctity) and Esoterism. Esoterism in contemporary culture acts as transformed sanctity. The feeling of holiness is indispensable for human existence – the every spiritual crisis then traditional religiousness loses its power to organize and support spiritual nature of human existence opens the door for esoteric modifications of sacrum. Esoterism through the prism of Religion is an attempt of religious consciousness for individual awareness of deity – thereby esoteric experience is very close to religious one. Eastern Religions reveals themselves in Postmodernism as esoteric variations of sacrum, manifestations of chthonic nature where they are also affected by other tendencies of Western postmodern consciousness:Eastern Esoterismturns to widely usable exoticism – Egsoterism – hidden becomes popular, freely available and explorable. The reflection of East and West in the oeuvre of Jurga Ivanauskaitė is being developed by the principle of thesis/antithesis that contains the majority of postmodern implications. The East through writer’s eyes is seen as a quintessence of spiritual essence opposite to the West that, on the contrary, is filled by means of deconstruction and desacralization. J. Ivanauskaitė’s addiction to Esoterism asserts not only in the field of poetics, but also in her individual existence as a general motivation to seek enlightenment, hidden significance, as a faith in source of unique knowledge and mystery that is possible to achieve.